Influence of lipophilicity on the interactions of hydroxy stilbenes with cytochrome P450 3A4 - Regev-Shoshani G.; Shoseyov, O.; Kerem, Z.
Resveratrol, a polyphenol found in red wine, was recently suggested to act as an irreversible, mechanism-based inactivator of cytochrome P450 3A4 (CYP3A4). We found a significant inhibition of human CYP3A4-dependent transformation of cyclosporine by resveratrol, with IC50 = 4.5 lM. We studied the kinetics parameters of CYP3A4 transformation of resveratrol and structurally related, naturally occurring stilbenes. Resveratrol, piceid, resveratroloside, 5,40-dihydroxy-3-O-methoxystilbene, and 5,3-dihydroxy-40-O-methoxystilbene were all shown to inhibit hydroxylation of testosterone by CYP3A4. Both methoxy-stilbenes had lower IC50 values, ranging from 0.43 to 0.47 lM, suggesting that lipophilicity rather than number or positions of free hydroxyls (3,5 or 5,40)determines the CYP3A4 inhibition capacity of polyphenols. In line with these findings, both glucosyl-stilbenes were found to be weak inhibitors of CYP3A4. The affinity of the enzyme towards methoxy-stilbenes, expressed as apparent Km, was indeed higher than those for the parent resveratrol and its glucosides, in CYP3A4 reaction mixtures. Vmax values were similar, except for piceid. These results support the role of lipophilicity in the interaction of polyphenols with CYP3A4. It is suggested that selective structural modifications of substrates add significantly tof knowledge acquired through molecular modifications of the enzyme.
Keywords: RESVERATROL; CYP3A4; PICEID; KINETICS; CYCLOSPORINE; POLYPHENOLS